High rate lithium-sulfur battery enabled by sandwiched single ion conducting polymer electrolyte - Sun, Yubao (Sci Rep, 2016)
Lithium-sulfur batteries are highly promising for electric energy storage with high energy density, abundant resources and low cost. However, the battery technologies have often suffered from a short cycle life and poor rate stability arising from the well-known “polysulfide shuttle” effect. Here, we report a novel cell design by sandwiching a sp(3) boron based single ion conducting polymer electrolyte film between two carbon films to fabricate a composite separator for lithium-sulfur batteries. The dense negative charges uniformly distributed in the electrolyte membrane inherently prohibit transport of polysulfide anions formed in the cathode inside the polymer matrix and effectively blocks polysulfide shuttling. A battery assembled with the composite separator exhibits a remarkably long cycle life at high charge/discharge rates.